Problems on rural development in Southern Nigeria - Takes C.A.P; Nigerian Institute of Social and Economic Research (NISER) (Lagos : Nigerian Institute of Social and Economic Research (NISER), 1964)
This paper examines problems impeding developments in the communities in the rural areas of the southern part of Nigeria. The research was carried out by Takes, Charles Antoine Peter and sponsored by the Nigerian Institute of Social and Economic Research (NISER). The findings recommends likely solution to alleviate the living standard of the people in the region.
asm; 15/04/19
Loans
Keywords: Rural conditions; Rural development; Nigeria; Nigeria-Sourthern